Cotrimoxazole treats fluoroquinolone-resistant Salmonella typhi H58 infection - Karki, M; Pandit, S; Baker, S; Basnyat, B (BMJ Publishing Group, 2016)
A woman aged 20 years presented with fever and no localising signs. She was treated with cotrimoxazole and the subsequent blood culture was positive for Salmonella typhi (S. typhi), which was resistant to fluoroquinolones but susceptible to cotrimoxazole. Genotyping identified an FQ-R subclade of H58 S. typhi Fever clearance time was 4 days after starting the antibiotics, and no relapses were noted on 2 months of follow-up. This inexpensive, well-known and easily available antimicrobial could be suitably redeployed for fluoroquinolone-resistant enteric fever in South Asia.